CEO sexual scandals and corporate decisions. - Wong, Wai Hang. (2012)
We used reported CEO sex scandals as a proxy for lack of self-control and examined the effects of this deficiency on corporate decisions. We found that stock markets react negatively to news of sexual scandal and the CEOs are more likely to be fired afterwards. We found that CEOs with sexual scandal make more acquisitions and borrow less in the firm’s capital structure. These facts are consistent with the view that CEO short of self control make more aggressive acquisition decisions and are averse to the debt disciplining. Overall, our paper shows that the personal attributes of CEO, like a lack of self-control, are important in determining corporate policies.